A nursing innovation to promote healthy bowel functioning in children. Issue 2 (April 2022) - Reid-Searl, Kerry; Anderson, Carina; Crowley, Kate; Blunt, Nicole; Cole, Rachelle; Suraweera, Dayani
ABSTRACT: Background: Constipation affects up to 30% of children world-wide and if not managed effectively, this condition can progress into adult years. Constipation in children can result in physical and psychosocial concern. One way to help reduce constipation in children is for nurses and health care professionals, who are working with children, to put strategies in place that enable children to gain an awareness of their own bowel functioning and ways to promote healthy stools. Aim: The aim of this study was to design and implement an educational resource for children between the ages of four and -8 years about healthy bowel functioning and to evaluate its effectiveness from a parent/ caregiver's perspective. Methods: This study used a convergent mixed methods approach to evaluate the effectiveness of the intervention 'The Poop it Kit'. Following ethical approval, 15 parents/caregivers were recruited for the study. After a period of 2-4 weeks of using 'The Poop it Kit' with children, participants were asked to complete a survey as well provide open-ended feedback. Findings: Results of the survey revealed that 'The Poop it Kit' was a fun and engaging resource for children. The kit improved children and parents'/caregivers' knowledge about healthy bowel habits and it influenced positive behavioural changes for children in ways to promote healthy bowel functioning. Discussion: Education to address constipation and ultimately the promotion of healthy bowel functioning begins with parents, caregivers and children feeling open to discuss the topic of poo (faeces) and what makes healthy poo. Nurses play a part in providing that education. Constipation is challenging for the child, and if not managed early can lead to problems such as overflow faecal incontinence. The design of 'The Poop it Kit' focused on ways to engage children and the resources were beneficial in educating children about healthy bowel habits. Conclusion: The creation of a resource for children relating to bowel functioning has been a step in the right direction. Improving bowel functioning begins with education. Empowering children with knowledge about their bowels begins with the creation of aged appropriate, fun and engaging resources that children and their caregivers can become immersed in.